Recent Advances in Electron Cryomicroscopy. Part A - Ludtke, Steven J.; Prasad, B. V. Venkataram; ScienceDirect eBooks (Amsterdam ; Boston : Academic Press/Elsevier, 2010)
Structural genomics is the systematic determination of 3-dimensional structures of proteins representative of the range of protein structure and function found in nature. The goal is to build a body of structural information that will predict the structure and potential function for almost any protein from knowledge of its coding sequence. This is essential information for understanding the functioning of the human proteome, the ensemble of tens of thousands of proteins specified by the human genome. While most structural biologists pursue structures of individual proteins or protein groups, specialists in structural genomics pursue structures of proteins on a genome wide scale. This implies large scale cloning, expression and purification. One main advantage of this approach is economy of scale. Key Features *Examines the three dimensional structure of all proteins of a given organism, by experimental methods such as X-ray crystallography and NMR spectroscopy * Looks at structural genomics as a foundation of drug discovery as discovering new medicines is becoming more challenging and the pharmaceutical industry is looking to new technologies to help in this mission.
From envelopes to atoms: the remarkable progress of biological electron microscopy -- Present and future of membrane protein structure determination by electron crystallography -- Single-particle applications at intermediate resolution -- Visualizing molecular machines in action: single-particle analysis with structural variability.
Text in English.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Cryomicroscopy; Electron microscopy; Proteins -- Structure; Biochemistry -- Methods; SCIENCE -- Electron Microscopes & Microscopy; Biochemistry; Cryomicroscopy; Electron microscopy; Proteins -- Structure; Electronic books